Transcription Factor Hepatocyte Nuclear Factor 6 Regulates Pancreatic Endocrine Cell Differentiation and Controls Expression of the Proendocrine Gene ngn3 - Jacquemin, Patrick (American Society for Microbiology, 2000)
Hepatocyte nuclear factor 6 (HNF-6) is the prototype of a new class of cut homeodomain transcription factors. During mouse development, HNF-6 is expressed in the epithelial cells that are precursors of the exocrine and endocrine pancreatic cells. We have investigated the role of HNF-6 in pancreas differentiation by inactivating its gene in the mouse. In hnf6(−/−) embryos, the exocrine pancreas appeared to be normal but endocrine cell differentiation was impaired. The expression of neurogenin 3 (Ngn-3), a transcription factor that is essential for determination of endocrine cell precursors, was almost abolished. Consistent with this, we demonstrated that HNF-6 binds to and stimulates the ngn3 gene promoter. At birth, only a few endocrine cells were found and the islets of Langerhans were missing. Later, the number of endocrine cells increased and islets appeared. However, the architecture of the islets was perturbed, and their β cells were deficient in glucose transporter 2 expression. Adult hnf6(−/−) mice were diabetic. Taken together, our data demonstrate that HNF-6 controls pancreatic endocrine differentiation at the precursor stage and identify HNF-6 as the first positive regulator of the proendocrine gene ngn3 in the pancreas. They also suggest that HNF-6 is a candidate gene for diabetes mellitus in humans.